Towards a Practical Centrality of Human Rights:: Primacy for the Dignities of Humans in the Prison System (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article addresses the tension between the theoretical plan and the plan for the implementation of fundamental human rights, with the Prison System as its background, going through the fundamental theories of human rights and verifying the practical adequacy of the critical theory of human rights to overcome the framework of ineffectiveness of human rights in the prison environment. For Joaquim Herrera Flores' critical theory of human rights, human rights are the result of the processes of struggle for the full exercise of human dignity, so, in this perspective, they are no longer postulated and become concrete products of social tensions. In this sense, we note the importance of the figure of Human Rights Defenders, as subjects who, in their individual or collective performance, lead these struggles in search of the promotion and realization of human rights. Therefore, a conscious and strategic action by these Defenders is fundamental, founded on a critical perspective of human rights, aiming to overcome this Incosntitutional State of Things.